Dose Effect of Polyethylene Microplastics Derived from Commercial Resins on Soil Properties, Bacterial Communities, and Enzymatic Activity - Lesbia Gicel Cruz; Fo-Ting Shen; Chiou-Pin Chen; Wen-Ching Chen (Microorganisms)
Soils are the largest reservoir of microplastics (MPs) on earth. Since MPs can remain in soils for a very long time, their effects are magnified. In this study, different concentrations of polyethylene (PE) MPs derived from commercial resins (0%, 1%, 7%, and 14%, represented as MP_0, MP_1, MP_7, and MP_14) were added to soils to assess the changes in the soils’ chemical properties, enzyme activities, and bacterial communities during a 70-day incubation period. The results show that PE MP treatments with low concentrations differed from other treatments in terms of exchangeable Ca and Mg, whereas at high concentrations, the pH and availability of phosphate ions differed. Fluorescein diacetate (FDA), acid phosphatase (ACP), and N-acetyl-β-d-glucosaminidase (NAG) enzyme activities exhibited a dose-related trend with the addition of the PE MPs; however, the average FDA and ACP activities were significantly affected only by MP_14. Changes in the microbial communities were observed at both the phylum and family levels with all PE MP treatments. It was revealed that even a low dosage of PE MPs in soils can affect the functional microbes, and a greater impact is observed on those that can survive in polluted environments with limited resources.